2010
DOI: 10.1016/j.rpor.2010.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetric and physical comparison of IMRT and CyberKnife plans in the treatment of localized prostate cancer

Abstract: Both systems have a very good ability to create highly conformal volumetric dose distributions. Median HI of PTV for IMRT and CK plans were 1.08 and 1.33, respectively (p < 0.001).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
2
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 30 publications
0
35
2
1
Order By: Relevance
“…Irradiation of patients using IMRT, VMAT, CK, and TT techniques is increasingly reported in the literature [16][17][18][19][20][21][22]. Despite the technological differences related to the geometry of generated beams: the changing shape of the beam field vs circular tubes, the dose distributions we obtain as a result of the calculations are very comparable, of course, for "small" cancerous changes.…”
Section: Resultsmentioning
confidence: 79%
“…Irradiation of patients using IMRT, VMAT, CK, and TT techniques is increasingly reported in the literature [16][17][18][19][20][21][22]. Despite the technological differences related to the geometry of generated beams: the changing shape of the beam field vs circular tubes, the dose distributions we obtain as a result of the calculations are very comparable, of course, for "small" cancerous changes.…”
Section: Resultsmentioning
confidence: 79%
“…The average homogeneity difference ratio value was 11.03 ± 17.2. In five patients, the IMRT plans were more inhomogenous than the CyberKnife plans, and in the remaining seven patients, the CyberKnife plans were more inhomogenous when compared with the corresponding IMRT plans [14].…”
Section: Dose To Testesmentioning
confidence: 90%
“…Our results are in accordance with a similar study done by Sabbir Hosaain, et al and Ceylan, et al [12][13] comparing these two modalities (CyberKnife and IMRT). However, in a study done by Shiu, et al comparing CyberKnife and IMRT dose distributions, they found the dose to critical organs were less in the IMRT plans [14]. RVR is less in all CyberKnife plans compared to the simulated IMRT plans reaching statistical significance at V100%(p=0.01), V95%(p=0.004), V90%(p=0.001), V80%(p=0.02), V70%(p=0.03), V60%(p=0.01), V50%(p=0.01), V40%(p=0.02), and V30%(p=0.001) levels indicating lower nonclinical target volume, non-organ at risk tissue exposure at these dose levels.…”
Section: Conformation Number (Cn) Is Defined Asmentioning
confidence: 96%
“…Dosimetric studies have compared treatment plans using different IMRT modalities in patients with prostate cancer [8][9][10][11][12] . The dosimetric outcome differed when comparing plans using RapidArc and the VMAT in comparison to IMRT in the treatment of prostate cancer [13][14][15][16][17][18][19][20][21][22][23][24] .…”
Section: Introductionmentioning
confidence: 99%